2014
DOI: 10.1177/0885328214556913
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal stress triggered by near infrared-irradiated carbon nanotubes promotes bone deposition in rat calvarial defects

Abstract: The bone regenerative healing process is often prolonged, with a high risk of infection particularly in elderly and diseased patients. A reduction in healing process time usually requires mechanical stress devices, chemical cues, or laser/thermal therapies. Although these approaches have been used extensively for the reduction of bone healing time, the exact mechanisms involved in thermal stress-induced bone regeneration remain unclear. In this study, we investigated the effect of optimal hyperthermia on rat c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…20). NIR irradiation significantly up-regulated the expression of HSP 70 in Apt-bioinspired MVs cultured osteoblasts, which can be ascribed to the good photothermal performance of the BPQDs in Apt-bioinspired MVs 2529 . Taken together, the above results confirm that the Apt-bioinspired MVs with photothermal effect can promote biomineralization and the expression of proteins, such as ALP, Runx2, and HSP 70 plays essential roles in the biomineralization process.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…20). NIR irradiation significantly up-regulated the expression of HSP 70 in Apt-bioinspired MVs cultured osteoblasts, which can be ascribed to the good photothermal performance of the BPQDs in Apt-bioinspired MVs 2529 . Taken together, the above results confirm that the Apt-bioinspired MVs with photothermal effect can promote biomineralization and the expression of proteins, such as ALP, Runx2, and HSP 70 plays essential roles in the biomineralization process.…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, ultrasmall BP nanosheets with sizes of several nanometers (usually named as BP quantum dots, BPQDs) have high photothermal conversion efficiency and thus can be used as a promising photothermal agent 24 . Previous researches have indicated that hyperthermia promotes biomineralization by stimulating the up-regulated expression of proteins, including alkaline phosphatase (ALP) and heat shock proteins (HSP) 2529 , thus increasing the generation of mineral crystals and realizing bone reconstruction 2931 . These special properties render BPQDs promising biomaterials for stimulating biomineralization and further promoting mineralization-guided biological behavior regulation and medical engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches have demonstrated that mild localized heat can efficiently stimulate cell proliferation and induce rapid in situ bone regeneration in vivo. [102][103][104] BP nanomaterials have high photothermal conversion efficiency. This property of BP nanomaterials can be used for both antitumor and tissue regeneration applications.…”
Section: -mentioning
confidence: 99%
“…Compared with HA, the advantages of BP are as follows: 1) BP can be degraded into non-toxic phosphate after oxidation, then attract surrounding free calcium ions and combine into calcium phosphate mineralization and deposition to promote in-situ bone regeneration and repair [ 128 ]; 2) Due to the strong light absorption ability of BP in the NIR region, BP-based nanomaterials have a stable, damage-free light-controlled adjustment release mode, which makes the release of loaded drugs more stable and longer-lasting [ 49 ]; 3) In addition, there have been numerous studies showing that BP has good capability of photothermal conversion under NIR region and local hyperthermia treatment has also been confirmed to up-regulate alkaline phosphatase (ALP) [ 129 , 130 ], heat shock protein (HSP) [ 131 ], to increase the formation of mineralized crystal, and to achieve longitudinal and concentric growth of bone, thereby accelerating the process of bone repair [ 132 , 133 ]. ALP is the main marker that reflects bone metabolic capacity and its level is related to the differentiation of osteoblasts and greatly affects the process of osteoblast cell matrix mineralization [ 134 ].…”
Section: The Destination Of Bp Tissue Engineering Application-bone Thmentioning
confidence: 99%